Mortality rates from suicide among Brazilian teachers: base year 2020 (Olhar de Professor, 2024)
The increasing incidence of suicides among teachers in Brazil reveals a concerning reality that demands detailed analysis and the urgent implementation of effective preventive measures. This article investigates suicide data among Brazilian teachers by analyzing the 2020 edition of the Ministry of Health's Mortality Information System database. This cross-sectional, quantitative-descriptive study examined 1,556,824 death notifications for the Brazilian population. In 2020, Brazil reported 13,835 suicide cases, equating to one self-inflicted death for every 112 fatalities. Among teachers, of the 13,351 recorded deaths, 142 were suicides, which translates to three cases per week. Therefore, it is essential to develop comprehensive suicide prevention strategies, including improvements in access and preventive care for educators through workers' mental health systems, making it a priority on the global public health agenda.
Keywords: Suicide; Mental health; Teacher